2020
DOI: 10.1101/2020.06.02.129247
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure of bacterial phospholipid transporter MlaFEDB with substrate bound

Abstract: In double-membraned bacteria, phospholipids must be transported across the cell envelope to maintain the outer membrane barrier, which plays a key role in antibiotic resistance and pathogen virulence. The Mla pathway has been implicated in phospholipid trafficking and outer membrane integrity, but the mechanism by which this ABC transporter facilitates phospholipid transport remains unknown. Here we report the cryo-EM structure of the MlaFEDB inner membrane complex at 3.05 Å resolution. Our structure reveals t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 73 publications
3
21
0
Order By: Relevance
“…On the other hand, prior studies indicated that the Mla system is an importer (Malinverni and Silhavy, 2009;Chong, Woo and Chng, 2015;Powers and Trent, 2018;Yeow et al, 2018), and in vitro reconstitution and transport assays suggest that MlaFEDB may be bi-directional, with a preference for import (retrograde transport) (Tang et al, 2020). Concurrently with our preprint, two other groups also reported structures of the MlaFEDB complex on BioRxiv (Coudray et al, 2020;Mann et al, 2020;Tang et al, 2020), and these structures appear to be similar overall, although the PDB coordinates…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…On the other hand, prior studies indicated that the Mla system is an importer (Malinverni and Silhavy, 2009;Chong, Woo and Chng, 2015;Powers and Trent, 2018;Yeow et al, 2018), and in vitro reconstitution and transport assays suggest that MlaFEDB may be bi-directional, with a preference for import (retrograde transport) (Tang et al, 2020). Concurrently with our preprint, two other groups also reported structures of the MlaFEDB complex on BioRxiv (Coudray et al, 2020;Mann et al, 2020;Tang et al, 2020), and these structures appear to be similar overall, although the PDB coordinates…”
Section: Discussionsupporting
confidence: 71%
“…Three replicates of the experiment were performed, starting with protein expression. NB: earlier protocols using urea solubilization (Coudray et al, 2020) gave globally similar results but with variation in cross linking efficiency between biological replicates; the improved protocol used here,…”
Section: Lipid Crosslinking Experimentsmentioning
confidence: 72%
“…While this manuscript was under review, three independent groups released the structure of the Escherichia coli MlaBDEF complex (MlaBDEFec), in a range of nucleotide states and with various solubilization approaches (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…A spectacular high resolution example is provided by the cryo‐EM structure of the phospholipid ABC transporter, MlaFEDB, in Nanodics formed with MSP1D1 and an E. coli polar lipid extract (PDB http://firstglance.jmol.org/fg.htm?mol=6XBD) that explicitly resolves the encircling MSP (Figure 3a). 112 This transporter was found with two lipid molecules bound as substrates, which may indicate transport of two lipids in each catalytic cycle, or involvement of this transporter in the transport of cardiolipin, which has four acyl chains.…”
Section: Introductionmentioning
confidence: 94%
“…(a) Cryo‐electron microscopy (cryo‐EM) structure of the ABC transporter complex MlaFEDB. Hexamer MLAD (yellow), dimeric transport permease MLAE (red), ATP binding protein (cyan) and transporter‐binding protein MLAB (blue) are enclosed into MSP1D1 Nanodisc (two parallel helices shown in green) 112 . (b) Cryo‐EM structure of connexin‐46/50 incorporated in two Nanodiscs (light gray contours).…”
Section: Introductionmentioning
confidence: 99%